Motivation of out-of-field teachers for participating in professional development courses in mathematics. Issue 5 (20th October 2021) - Lünne, Steffen; Schnell, Susanne; Biehler, Rolf
ABSTRACT: Increasing need for mathematics teachers in secondary schools has led to the implementation of professional development courses (PDC) offering formal certifications for in-service teachers in some German states. While these PDCs are well attended, little is known about the motives why teachers participate. In this article, we present data from a questionnaire (n = 61) with mainly open questions conducted at the beginning of three iterations of a yearlong PDC. Findings indicate a variety of extrinsic and intrinsic incentives for participating in the PDC. An additional cluster analysis hints at three groups of participants which differ mainly in regard to their orientation towards professional development, their interest in mathematics and their extrinsic motivation.